The Dirac equation in the Bertotti-Robinson space-time - Sakalli, I (Kluwer Academic/Plenum Publ, 2003)
The Dirac equation is considered in the uniform electromagnetic field space of Bertotti-Robinson with charge coupling. The methods of separation of variables and decoupling are easily achieved. The separated axial equation is reduced to a rare Riccati type of differential equation. The behaviour of potentials, their asymptotic solutions and the conserved currents of the Dirac equation are found.
Keywords: Bertotti-Robinson space-time; Dirac equation